2019
DOI: 10.1136/heartasia-2018-011143
|View full text |Cite
|
Sign up to set email alerts
|

Validation of a questionnaire measuring patient knowledge of atrial fibrillation in an Asian cohort

Abstract: BackgroundPoor patient understanding of atrial fibrillation (AF) may contribute to underuse of anticoagulation. There are no validated instruments to measure patient knowledge in Asian cohorts. This study aims to validate a disease-specific questionnaire measuring the level of understanding of AF and its treatment among patients with AF in Singapore.MethodsA 10-item interviewer-administered questionnaire was created based on previously published questionnaires. Face and content validity were assessed. 165 part… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 26 publications
0
5
0
Order By: Relevance
“…A similar protocol was used by Bodar in the Physicians' Health Study 16 . Moreover, a disease characteristic and disease-specific treatment are among the most important factors identified in a recent questionnaire designed to measure patient knowledge of AF 37 . In the SUN cohort, the participation of university graduates (55% from health professions), and the confirmation of cases by a cardiologist minimizes the possibility of false positives.…”
Section: Discussionmentioning
confidence: 99%
“…A similar protocol was used by Bodar in the Physicians' Health Study 16 . Moreover, a disease characteristic and disease-specific treatment are among the most important factors identified in a recent questionnaire designed to measure patient knowledge of AF 37 . In the SUN cohort, the participation of university graduates (55% from health professions), and the confirmation of cases by a cardiologist minimizes the possibility of false positives.…”
Section: Discussionmentioning
confidence: 99%
“…Patient-reported outcomes were measured with questionnaires validated in Singapore for both English and simplified Chinese. AF-specific QoL was measured through the Atrial Fibrillation Effect on QualiTy-of-life (AFEQT) questionnaire [25], AF knowledge through the Singapore Atrial Fibrillation Knowledge Scale (SGAFKS) [26], and patient satisfaction through the modified Patient Satisfaction Questionnaire (PSQ) [27]. Depression was screened, and its severity was quantified with the Patient Health Questionnaire (PHQ-9) [28].…”
Section: Outcome Measures and Data Collectionmentioning
confidence: 99%
“…It has been demonstrated that higher levels of AF-related knowledge not only improve therapy uptake and adherence but also reduce AF-related complications such as stroke, thrombotic events, as well as health-care related costs and rate of hospitalizations [73]. Two multinational surveys showed that more than half of the patients with AF had low levels of knowledge about the increased risk of stroke related to AF or did not even know the name of their condition [192,193]. A recent European Heart Rhythm Association (EHRA) survey showed there is still room for improvement in education of patients taking OACs, mainly for NOACs [194].…”
Section: Medication Adherencementioning
confidence: 99%
“…Two multinational surveys showed that more than half of the patients with AF had low levels of knowledge about the increased risk of stroke related to AF or did not even know the name of their condition [ 192 193 ]. A recent European Heart Rhythm Association (EHRA) survey showed there is still room for improvement in education of patients taking OACs, mainly for NOACs [ 194 ].…”
Section: Anticoagulant Therapy To Prevent Af-related Strokementioning
confidence: 99%